Training on Utilization of Baby Diaper Waste into Resin Handicraft Products to Improve Community Economy: Pelatihan Pemanfaatan Limbah Popok Bayi Menjadi Produk Handicraft Resin untuk Peningkatan Perekonomian Masyarakat - Sri Purwati; Nancy Oktyajati; Sitti Mukarromah; Ricky Adi Saputra; Irvan Wananda Febriansyah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Baby diaper waste is a critical environmental issue, especially in areas with limited waste management. This program aims to transform baby diaper waste that is usually considered worthless into creative products with high economic value and reduce the volume of waste disposed of in landfills. This activity was implemented in Kitiran Climate Village RW VIII Purwosari Village, Surakarta, which provided support and active participation. The implementation method consisted of two main stages: socialization and lectures, followed by practice. The socialization and lecture sessions provided an understanding of the impact of baby diaper waste on the environment, the importance of waste treatment, the selection of resin handicraft as a solution, existing waste treatment methods, and an economic analysis showing the potential profitability of the product. After the lecture, participants followed the practice of making resin handicrafts which included separating waste from super absorbent polymer (SAP) materials, washing, soaking with disinfectants, drying, chopping, coloring, drying, making resin handicrafts products, and finishing. The results showed an increase in community skills in processing baby diaper waste and an increase in income from the sale of resin handicraft products. This program is expected to reduce the volume of baby diaper waste disposed to landfill, increase environmental awareness, and contribute to the community's economy.